2005
DOI: 10.1007/s10708-005-3926-1
|View full text |Cite
|
Sign up to set email alerts
|

Contesting Chinatown: Place-making and the Emergence of ‘Ethnoburbia’ in Brisbane, Australia

Abstract: This paper juxtaposes the actual areas of settlement and settlement activities of Chinese migrants in Brisbane's southern suburbs since the mid-1980s, with the concomitant, Ôgovernment planned' construction of the city's Chinatown as an Ôexotic,' Ôethnic,' and Ôcosmopolitan' landmark. It argues that while the latter, as with Chinatowns in other Australian and world cities, has continued to appropriate the symbols of so-called ÔChineseness' to sell the locale to non-Chinese, the former, in recalling the notion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 6 publications
(2 reference statements)
1
29
0
Order By: Relevance
“…The suburb chosen had to be near good education, transport and shopping centres. This supports other studies that have focused on recent Chinese immigration, mostly in the US (Li 1998; but also in Australia (Ip 2005). Recent Chinese migrants preferred to conceal their ethnic identity and not show it through their houses, as often described in the literature about migrants from south and east Europe, because unlike in the post-war decades, they were not expected to forgo their cultural heritage.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The suburb chosen had to be near good education, transport and shopping centres. This supports other studies that have focused on recent Chinese immigration, mostly in the US (Li 1998; but also in Australia (Ip 2005). Recent Chinese migrants preferred to conceal their ethnic identity and not show it through their houses, as often described in the literature about migrants from south and east Europe, because unlike in the post-war decades, they were not expected to forgo their cultural heritage.…”
Section: Resultssupporting
confidence: 87%
“…The most important features desired in a house for most participants, as also in Brisbane (Ip 2005), were not its size or garden but the high quality of education in the suburb, public transport and proximity to shopping centres and workplaces, and only then was the house itself considered if it were within the price range. Previously, most apartments in China had been appreciated because of their location and close proximity to urban facilities such as shopping centres and public amenities.…”
Section: The Desire To Improve Future Opportunitiesmentioning
confidence: 99%
“…Rishbeth () also noted the potential for tension between different groups within a neighbourhood (in this case, newcomers and an established local community) when placemaking practices involve public spaces, arguing that in neighbourhoods with high concentrations of different ethnicities, planners must meaningfully engage with each community. Ip (, p. 73) found that the government‐planned Chinatown in Brisbane, Australia was a contested ground for Chinese placemaking against ‘the imagination of mainstream society’. This critique is similar to Anderson's () description of Vancouver's Chinatown as a Western creation of ‘Chineseness’.…”
Section: Placemaking Through Ethnic Entrepreneurshipmentioning
confidence: 99%
“…Choi (1975, p. 67) estimates that in the mid-1960s, most Chinese-Australians were located in the capital cities (83 per cent), with almost half located in Sydney alone (45.8 per cent). And there was never, for example, a long-established Chinatown within Brisbane (Ip 2006). 1959-65 1965-70 1970-75 1975-80 1980-85 1985-1990 1990-95 1995-00 2000-02 …”
Section: The Hong Kong Chinese Presence In Australiamentioning
confidence: 99%
“…Historically Sydney has always been the iconic city of Australia and thus a magnet for Chinese migrants for centuries, while Brisbane's appeal as a destination of migration did not emerge until the mid-1980s. Brisbane was historically a city that Chinese migrants bypassed as they moved to northern Queensland in search of gold (Ip 2006).…”
Section: Putting Transnationalism In Context 93mentioning
confidence: 99%